2020
DOI: 10.30574/gscbps.2020.12.3.0230
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Carissa edulis using stem cuttings for domestication and conservation in Uganda

Abstract: Carissa edulis is a plant of 5m high at maturity. It grows in the Savannah woodlands of Uganda and is commonly found on ant-hills. Carissa edulis is used as a remedy for treatment of headache, chest complains, rheumatism, oedema, gonorrhea, syphilis, sickle cell anaemia, cough, ulcer, tooth-ache, and worms. Poor harvesting methods of Carissa edulis for medicine such as uprooting the whole plant threatens its existence. Its seeds are scarce because ants, birds and animals eat them hence propagation by seed is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sand and coco-peat have high porosity than soil mix resulting in easy elongation of roots in such media. Abigaba et al (2020) found that sterilized sand as propagating medium for softwood cuttings of Carissa edulis resulted in better propagation, while Nurhayati et al (2020) successfully propagated Cinnamomum zeylanicum plants in the coco-peat medium. Overall, in the present study, both sand and coco-peat gave better propagation results.…”
Section: Resultsmentioning
confidence: 99%
“…Sand and coco-peat have high porosity than soil mix resulting in easy elongation of roots in such media. Abigaba et al (2020) found that sterilized sand as propagating medium for softwood cuttings of Carissa edulis resulted in better propagation, while Nurhayati et al (2020) successfully propagated Cinnamomum zeylanicum plants in the coco-peat medium. Overall, in the present study, both sand and coco-peat gave better propagation results.…”
Section: Resultsmentioning
confidence: 99%